S15.1 Hydroxychloroquine daily dose, hydroxychloroquine blood levels and the risk of flares in patients with systemic lupus erythematosus. (27th September 2022) - Fasano, S; Messiniti, V; Gaggiano, E; Milone, A; Patrone, M; Riccio, F; Ciccia, F
Abstract : Background: Recent guidelines for Systemic Lupus Erythematosus (SLE) recommend using a hydroxychloroquine (HCQ) dose less than 5.0 mg/kg/day to reduce the risk of HCQ-induced retinopathy. The aims of our study were to (1) evaluate if HCQ reduction dose to 5 mg/kg/day is associated with increased risk of SLE flares, (2) compare HCQ blood levels between the two different oral dosages, and (3) evaluate if HCQ reduction dose to 5 mg/kg/day is associated with reduced risk of retinopathy in SLE. Methods: We identified a cohort of patients with SLE taking HCQ for at least 6 months and followed for 24 months. At study entry and six months later a blood venous sample was taken to measure whole blood concentration of HCQ by liquid chromatography-tandem mass spectrometry. A mean HCQ value for each patient was then calculated. The primary outcome of interest of this study was the occurrence of flares. Flares were defined by SELENA-SLEDAI Flare Index. Incidence of new SLE flares after recruitment was put in relation to daily HCQ dose according to body weight and mean HCQ blood levels. Cox regression analysis served to identify factors associated with SLE flares occurrence in the overall cohort in patients according to HCQ dose. Results: Of 83 patients with SLE taking HCQ, 17 (20%) were excluded because of poor therapeutic adherence. All the remaining 66 patients were Caucasian, mostly female (99%), with a mean age of 42 (±11.2) years. We stratified patients according to HCQ oral dose in two groups: ≤5 mg/kg versus >5 mg/kg per day. The HCQ dose of ≤5 mg/kg per day was assumed by 27 (41%) patients, with median HCQ blood levels of 580.8 ng/mL. The proportion of patients with HCQ blood levels≥ 500 ng/ml (therapeutic range) was 51% (14/27). We observed 11(16%) flares that developed in mean 14, 8 months of follow up. A total of 7/27 (26%) patients taking <5 mg/kg of HCQ had a flare. We registered only 4/39 (10%) flares in the other group, all mild/moderate flares, although the differences were not statistically significant (p=0.08). There was a trend for high HCQ dose being associated with a lower flare rate (12.3 events per 100 person-years) versus HCQ <5mg/Kg/day (43.5 events per 100 person-years). However, in patients treated with HCQ dose>5mg/Kg/day, therapeutic HCQ levels (>500 ng/ml) were associated with no occurrences of disease flares. At univariate analysis, older age at baseline was protective against flare occurrence (HR 0.93) while concomitant immunosuppressant therapy showed significant positive association (HR 3.66). We also observed that longer time on remission was associated with lower flare risk even if was not significant (p=0.05). No other significant associations were observed. In these patients, therapeutic HCQ levels were not associated with the occurrences of retinopathy. Conclusion: Patients with low HCQ dosage tend to have more flares, although the difference was not statistically significant. Monitoring HCQ levels might allow identification of early non-adherence. The risks and benefits must be balanced in choosing to reduce HCQ dose.